2022
DOI: 10.1186/s13059-022-02789-6
|View full text |Cite
|
Sign up to set email alerts
|

Retained introns in long RNA-seq reads are not reliably detected in sample-matched short reads

Abstract: Background There is growing interest in retained introns in a variety of disease contexts including cancer and aging. Many software tools have been developed to detect retained introns from short RNA-seq reads, but reliable detection is complicated by overlapping genes and transcripts as well as the presence of unprocessed or partially processed RNAs. Results We compared introns detected by 8 tools using short RNA-seq reads with introns observed in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“… 43 However, it has been challenging to quantify introns by short-read sequencing. 44 Using the long-read sequencing data of human cerebral organoids, we identified IRs by IRFinder-S 45 and compared IRs from different cell types. A total of 1,427 differentially retained introns (DRIs) were identified (∣ΔPIR∣ ≥ 5% and FDR < 0.05; Figure 3A ; Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 43 However, it has been challenging to quantify introns by short-read sequencing. 44 Using the long-read sequencing data of human cerebral organoids, we identified IRs by IRFinder-S 45 and compared IRs from different cell types. A total of 1,427 differentially retained introns (DRIs) were identified (∣ΔPIR∣ ≥ 5% and FDR < 0.05; Figure 3A ; Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is challenging to study IR using short-read sequencing due to repetitive sequences. 44 In principle, long-read sequencing covers the full transcript and provides a promising solution. Our analysis of human cerebral organoids uncovered over 1,400 differential IR events in oligoT-captured transcripts, suggesting the robustness.…”
Section: Discussionmentioning
confidence: 99%
“…Our detection of alternative splicing revealed that the most frequent splicing event types were skipped exon events (50.1%) and the least frequent were retained intron events (3.5%). While these proportions are expected in higher eukaryotes [41, 118123], it is important to note that short-read algorithms for detecting AS events are less likely to misassemble skipped exon events and can therefore identify them with high accuracy, but they suffer from poor precision with respect to RI detection [124, 125]. Accurately disambiguating real splicing events from background noise (such as partial transcript processing) is greatly facilitated by long-read sequencing technologies, which enable much more precise discovery and reconstruction of full-length isoforms, significantly improving the characterization of functional transcripts [126].…”
Section: Discussionmentioning
confidence: 99%
“…IR was also found to be the most abundant DAS events during heat stress in our study, though we did not observe a drastic increase in the number of IR, probably reflecting the limitation of our analysis. Moreover, it has been recently reported that IRs are not reliably detected by short RNA-sequencing reads compared to long RNA-sequencing reads [ 104 ]. In the future, to detect more novel transcripts, a combined assembly strategy that merges a reference-based assembly and de novo transcriptome assembly can also be applied to create a more comprehensive transcriptome for AS analysis, especially under specific stress conditions [ 105 ].…”
Section: Discussionmentioning
confidence: 99%